Mentoring and Segregation: Female-Led Firms and Gender Wage Policies - Ana Rute Cardoso; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2007)
We explore the impact of mentoring of females and gender segregation on wages using a large longitudinal data set for Portugal. Female managers can protect and mentor female employees by paying them higher wages than male-led firms would do. We find that females can enjoy higher wages in female-led firms, the opposite being true for males. In both cases is a higher share of females reducing the wage level. These results are compatible with a theory where job promotion is an important factor of wage increases: if more females are to be mentored, less promotion slots are available for males, but also the expected chance of a female to be promoted is lower.
Keywords: M52; D21; J31; J16; 330; female entrepreneurs; wages; gender gap; matched employer-employee data